2012
DOI: 10.1111/ppl.12010
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical abilities of robusta coffee leaves for acclimation to cope with temporal changes in light availability

Abstract: The effects of varying intensities of light on plants depend on when they occur, even if the total amount of light received is kept constant. We designed an experiment using two clones of robusta coffee (Coffea canephora) intercropped with shelter trees in such a way that allowed us to compare coffee bushes shaded in the morning (SM) with those shaded in the afternoon (SA), and then confronting both with bushes receiving full sunlight over the course of the day (FS). The SM bushes displayed better gas-exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
(46 reference statements)
1
13
0
2
Order By: Relevance
“…; Rodríguez‐López et al . ). These results suggest that guard cells are either fixing the carbon needed to produce the osmoticum required to open the stomatal pore via photosynthesis or alternatively have stored this carbon in another form, most likely in the vacuole, during the previous dark period.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Rodríguez‐López et al . ). These results suggest that guard cells are either fixing the carbon needed to produce the osmoticum required to open the stomatal pore via photosynthesis or alternatively have stored this carbon in another form, most likely in the vacuole, during the previous dark period.…”
Section: Discussionmentioning
confidence: 97%
“…2). Given that the epidermal fragments were harvested pre-dawn, this fast stomatal opening may be related to the circadian clock of the stomatal opening of plants growing under tropical conditions, in which rapid stomatal opening is observed in early morning (Antunes et al 2012;Rodríguez-López et al 2013). These results suggest that guard cells are either fixing the carbon needed to produce the osmoticum required to open the stomatal pore via photosynthesis or alternatively have stored this carbon in another form, most likely in the vacuole, during the previous dark period.…”
Section: Can Tobacco Guard Cells Produce All the Atp And Osmolytes Rementioning
confidence: 99%
“…Regarding to effects of shade on vegetative growth and yield of coffee plants, studies have reported that shade causes an increased leaf area (RODRÍGUEZ-LÓPEZ et al, 2013), decreases in branch emission (MORAIS et al, 2006), increases in the internode distance (ANIM-KWAPONG et al, 2010), and etiolation of the plagiotropic and orthotropic branches (ARAÚJO et al, 2016). About the production of Coffea canephora under shading, few studies were performed in field conditions, even that exist a demand for this information, leaving a gap of uncertainties to the coffee producer that pretends to have a coffee plantation shaded.…”
Section: Introductionmentioning
confidence: 99%
“…higher efficiency in the use of nitrogen, and water, and enhanced potential net photosynthesis) (Machado Filho et al, 2012;Rodríguez-López et al, 2013), probably related to the reduction of temperature and irradiance level, as well as with an increase in air relative humidity . Figure 16.…”
Section: Intercropping and Afforestation System Of Plantingmentioning
confidence: 99%
“…Several works have reported that this system management might promote micro-meteorological changes, namely, by reducing (i) direct irradiation, (ii) wind velocity, (iii) air temperature, (iv) water vapor pressure deficit between the air and the leaf; which altogether would increase the water availability (DaMatta et al, 2003;2007b;2010;DaMatta 2004;DaMatta and Ramalho, 2006;Pezzopane et al, 2008;2011;Rodríguez-López et al, 2013). For instance, the positive effects of shading have been associated with the decrease of incident radiation on the canopy, reducing the extension of the photo-oxidative damages, the velocity of the wind and the temperature of the air (up to 5 ºC).…”
Section: Intercropping and Afforestation System Of Plantingmentioning
confidence: 99%